2000
DOI: 10.1002/(sici)1097-0185(20000601)259:2<168::aid-ar7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 expression during early avian cardiac and neural crest morphogenesis

Abstract: Matrix metalloproteinase-type 2 (MMP-2) degrades extracellular matrix, mediates cell migration and tissue remodeling, and is implicated in mediating neural crest (NC) and cardiac development. However, there is little information regarding the expression and distribution of MMP-2 during cardiogenesis and NC morphogenesis. To elucidate the role of MMP-2, we performed a comprehensive study on the temporal and spatial distribution of MMP-2 mRNA and protein during critical stages of early avian NC and cardiac devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 63 publications
5
87
2
1
Order By: Relevance
“…55,109 Other studies showed that a subset of NC cells in the hindbrain at the origin of the cardiac NC do not produce MMP-2 by themselves but use for migration MMP-2 released in their environment by mesodermal cells. 110,111 As mentionned before, NC cells also synthesize ADAM proteases such as ADAM-10 in the chick 91 and ADAM-13 in the frog. 112 Furthermore, ADAM-13 has been shown to cleave fibronectin and proposed to facilitate cell migration by reorganizing locally the fibronectin network.…”
Section: Molecular Players Of Emt In Nc Cellsmentioning
confidence: 78%
“…55,109 Other studies showed that a subset of NC cells in the hindbrain at the origin of the cardiac NC do not produce MMP-2 by themselves but use for migration MMP-2 released in their environment by mesodermal cells. 110,111 As mentionned before, NC cells also synthesize ADAM proteases such as ADAM-10 in the chick 91 and ADAM-13 in the frog. 112 Furthermore, ADAM-13 has been shown to cleave fibronectin and proposed to facilitate cell migration by reorganizing locally the fibronectin network.…”
Section: Molecular Players Of Emt In Nc Cellsmentioning
confidence: 78%
“…In addition to the structural rearrangements, delamination of NC cells and active migration throughout the whole embryo involves penetration of the basement membranes and invading extracellular matrices (ECM) (Fig.1 (Cai et al, 2000;Cantemir et al, 2004;Duong and Erickson, 2004). Also expression of several members of the novel metalloproteinase/disintegrin family ADAM identified in cancer have been reported in Xenopus cranial NC cells (Alfandari et al, 2001;Gaultier et al, 2002;Smith et al, 2002;Harrison et al, 2004).…”
Section: Modulation Of Extracellular Matrixmentioning
confidence: 99%
“…1d,e,j,n) and some of these cells are apparently neural crest cells, based on HNK-1 labeling or the known location of neural crest cells from chick/quail chimera studies (Fig. 2g-I;Noden, 1982;Lumsden et al, 1991;Cai et al, 2000).…”
Section: Mmp-2 Expression In Cells Of the Neural Crestmentioning
confidence: 99%
“…Several developmental events have been correlated with, or shown to depend on, proteolytic activity, including branching morphogenesis (Talhouk et al, 1991;Sympson et al, 1994;Lim et al, 1995;Lelongt et al, 1997), syntrophoblast invasion of the uterine wall (Harvey et al, 1995;Lefebvre et al, 1995;Alexander et al, 1996), neural crest cell migration (Valinsky and Le Douarin, 1985;Erickson and Isseroff, 1989;Agrawal and Brauer, 1996), endocardial cushion cell migration (McGuire and Orkin, 1992;McGuire and Alexander, 1993;Alexander et al, 1997;Cai et al, 2000), and craniofacial histogenesis (Chin and Werb, 1997).…”
Section: Introductionmentioning
confidence: 99%